2017
DOI: 10.1186/s12944-017-0598-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy improves body composition and alleviates insulin resistance in obesity related acanthosis nigricans

Abstract: BackgroundAcanthosis nigricans (AN) has a close relationship with obesity. It is believed that obesity and AN have the common pathophysiological basis such as hyperinsulinism. This study is aimed to observe the effect of laparoscopic sleeve gastrectomy (LSG) on body composition and insulin resistance in Chinese obese patients with acanthosis nigricans.MethodsA total of 37 obese patients who underwent LSG in our hospital were selected for analysis. They were divided into simple obesity (OB n = 14) and obesity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Bariatric surgery is the most effective treatment option for severe obesity and its associated comorbidities . Zhang et al . also revealed significant improvement in skin condition and severity of AN after LSG.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Bariatric surgery is the most effective treatment option for severe obesity and its associated comorbidities . Zhang et al . also revealed significant improvement in skin condition and severity of AN after LSG.…”
Section: Discussionsupporting
confidence: 61%
“…Bariatric surgery is the most effective treatment option for severe obesity and its associated comorbidities. 13 Zhang et al 6 also revealed significant improvement in skin condition and severity of AN after LSG. Consistently, we observed substantial weight reduction and improvement in skin condition and severity of AN in obese Chinese men with AN.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this study, all 23 patients had noticeable improvement in AN at a 3-month follow up, likely due to improved insulin resistance and fat loss. 13 We present a case of a 33-year-old African American woman who presented with a chief complaint of dark discoloration on her face. Physical exam revealed dark brown symmetric velvety thin plaques on the bilateral cheeks consistent with AN.…”
Section: Impact Of Lifestyle Changes On Acanthosis Nigricansmentioning
confidence: 99%